Post-extraction dimensional changes: A systematic review and meta-analysis (2021)
Aim To analyse the evidence pertaining to post‐extraction dimensional changes in the alveolar ridge after unassisted socket healing. Materials and Methods The protocol of this PRISMA‐compliant systematic review (SRs) was registered in PROSPERO (CRD42020178857). A literature search to identify studies that fulfilled the eligibility criteria was conducted. Data of interest were extracted. Qualitative and random‐effects meta‐analyses were performed if at least two studies with comparable features and variables reported the same outcome of interest. Results Twenty‐eight articles were selected, of which 20 could be utilized for the conduction of quantitative analyses by method of assessment (i.e. clinical vs radiographic measurements) and location (i.e. non‐molar vs molar sites). Pooled estimates revealed that mean horizontal, vertical mid‐facial and mid‐lingual ridge reduction assessed clinically in non‐molar sites was 2.73 mm (95% CI: 2.36–3.11), 1.71 mm (95% CI: 1.30–2.12) and 1.44 mm (95% CI: 0.78–2.10), respectively. Mean horizontal, vertical mid‐facial and mid‐lingual ridge reduction assessed radiographically in non‐molar sites was 2.54 mm (95% CI: 1.97–3.11), 1.65 mm (95% CI: 0.42–2.88) and 0.87 mm (95% CI: 0.36–1.38), respectively. Mean horizontal, vertical mid‐facial and mid‐lingual ridge reduction assessed radiographically in molar sites was 3.61 mm (95% CI: 3.24–3.98), 1.46 mm (95% CI: 0.73–2.20) and 1.20 mm (95% CI: 0.56–1.83), respectively. Conclusion A variable amount of alveolar bone resorption occurs after unassisted socket healing depending on tooth type.